2019
DOI: 10.26508/lsa.201900444
|View full text |Cite
|
Sign up to set email alerts
|

TspanC8 tetraspanins differentially regulate ADAM10 endocytosis and half-life

Abstract: This study demonstrates that the tetraspanins Tspan5 and Tspan15 which directly associate with the metalloprotease ADAM10 have an opposite impact on its endocytosis and half-life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 47 publications
4
34
2
Order By: Relevance
“…In that study, an approximate 70% siRNA knockdown of ADAM10 in the HCT116 and U2OS cell lines reduced Tspan5 expression by 40%, and ADAM10 was shown to be important for trafficking of Tspan5 out of the ER (15). Our findings are also consistent with a very recent study showing that Tspan15 surface expression is reduced by 60% in ADAM10-knockout PC3 prostate cancer cells (29). In the current study, we investigated Tspan15 expression in the absence of ADAM10 by CRISPR/Cas9 knockout in three different cell lines, namely A549, HEK-293T and Jurkat.…”
Section: Discussionsupporting
confidence: 92%
“…In that study, an approximate 70% siRNA knockdown of ADAM10 in the HCT116 and U2OS cell lines reduced Tspan5 expression by 40%, and ADAM10 was shown to be important for trafficking of Tspan5 out of the ER (15). Our findings are also consistent with a very recent study showing that Tspan15 surface expression is reduced by 60% in ADAM10-knockout PC3 prostate cancer cells (29). In the current study, we investigated Tspan15 expression in the absence of ADAM10 by CRISPR/Cas9 knockout in three different cell lines, namely A549, HEK-293T and Jurkat.…”
Section: Discussionsupporting
confidence: 92%
“…3b). This finding confirms previous reports that ADAM10 undergoes constitutive internalization [13,36] and also indicates that GI promotes internalization of ADAM10.…”
Section: Gi-induced Adam10 Downregulation Coincides With Adam10 Releasupporting
confidence: 92%
“…Interestingly, anti‐tetraspanin antibodies and LEL proteins reduce S. aureus adhesion to host cells, and more recently, it was found that the short peptides derived from the LEL domain of CD9 could reduce S. aureus adhesion to epithelial cell lines, primary keratinocytes and 3D tissue engineered model of the human skin (Figure 2F) (Green et al, 2011; Ventress et al, 2016). Apart from host cell invasion, Tspan C8 contributes to the spread of S. aureus by promoting the trafficking of ADAM10 from the endoplasmic reticulum to host cell surface (Eschenbrenner et al, 2020). In fact, S. aureus secretes an α‐toxin that interacts with and activates the metalloprotease ADAM10, which has been shown to be a receptor for bacteria α‐toxin (Figure 2J) (Virreira Winter, Zychlinsky, & Bardoel, 2016).…”
Section: Tetraspanin‐dependent Invasion and Colonisation Of Host Cellmentioning
confidence: 99%